All-cause Mortality Due to Bacteremia during a 60-Day Non-Physician Healthcare Worker Strike. (12th September 2020) - Jansåker, Filip; Holm, Mona Katrine Alberthe; Gradel, Kim Oren; Knudsen, Jenny Dahl; Boel, Jonas Bredtoft; ,
Abstract: This study explored all-cause mortality of bacteremia diagnosed during a 60-day non-physician healthcare worker strike in 2008. A significant change, with 5.0% (95% confidence interval [CI] 1.2–8.7%, P < .01) absolute risk increase, was seen in 90-day mortality during the strike (n = 598) compared with the rest of the study period 2000–2015 (n = 75 647).